2007
DOI: 10.1021/jp073479r
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Acid Hydrolysis Mechanism of Esters Enforced by Strongly Acid Microemulsions

Abstract: A kinetic study was carried out on the acid hydrolysis of 4-nitrophenylacetate and 4-nitrophenyllaurate in water/HOT/isooctane microemulsions. The substitution of Na+ in the sodium salt of bis(2-ethylhexyl)sulfosuccinate by H+ has permitted us to obtain a functionalized surfactant (HOT) and, consequently, strongly acid microemulsions. The use of HOT-based microemulsions allows us to reach concentrations of H+ in the aqueous core corresponding to a Hammett acidity function of H0 = -2. The rate constant at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous studies in our laboratory have shown a mechanistic change in the acid hydrolysis of 4-nitrophenylacetate and 4-nitrophenyllaurate in HOT-based microemulsions. For low water contents ( W < 15), an A1 mechanism has been observed that changes to A2 for higher water contents.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies in our laboratory have shown a mechanistic change in the acid hydrolysis of 4-nitrophenylacetate and 4-nitrophenyllaurate in HOT-based microemulsions. For low water contents ( W < 15), an A1 mechanism has been observed that changes to A2 for higher water contents.…”
Section: Introductionmentioning
confidence: 81%
“…Direct conversion of the protonated substrate to the transition state (A1) is much less probable, though changes in acidity and water activity can lead to this mechanism. Previous studies in our laboratory have shown a mechanistic change in the acid hydrolysis of 4-nitrophenylacetate and 4-nitrophenyllaurate 13 in HOT-based microemulsions. For low water contents (W < 15), an A1 mechanism has been observed that changes to A2 for higher water contents.…”
Section: Introductionmentioning
confidence: 83%
“…The same authors have applied this technique to clarify the mechanism of ester hydrolysis for reactions that require such high acid concentrations to evolve that would be impossible to achieve by other means [11]. The equilibrium and the pH-dependent complexation reaction in aqueous solution of the chromophoric anion murexide (Mu À ) with nickel ion have been used to assess fast reactions involving T-jump [12] and Pjump [13] relaxation measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists extensive evidence of the ability of microemulsions to influence reaction rates and equilibria, e.g., the hydrolysis of hydroxamic acids and other carboxylic acid derivatives . Interesting reports exist in literature on the kinetics of chemical reactions on microemulsions. , Prediction and/or interpretation of the kinetic influence of these media are relatively easy when the reagents congregate in the aqueous micro droplets that act as variable size nanoreactors concentrating the reagents …”
Section: Introductionmentioning
confidence: 99%